The rate of encrustation of biofouling organisms on experimental floating net-cages in tropical coastal waters - Cheah, S. H.; Chua, T. E. (E. G. Silas, 1980)
The rate of encrustation of biofouling organisms on experimental net frames in relation to position of the frames and mesh size was studied. From the investigation on the rate of encrustation of biofouling organisms in relation to position of the frames, it was observed that the species composition in the net of both frames were similar. The initial biofoulers on both frames were similar, they being Crypstosula, barnacles and tubeworms, At the peak of encrustation, the net of the vertical frame was encrusted with mainly Symplegma, whereas the net of the horizontal frame was mainly encrusted with Cryptosula, Generally, the net of the vertical frame was more encrusted than that of the horizontal frame. The species composition on the wood of both frames were similar. The initial biofouler on the frames were Cryptosula and barnacles. At the peak of encrustation, the wood of both frames were encrusted with mainly Cryptosula, barnacles and tubeworms. Generally, the wood of the horizontal frame was more encrusted than that in the vertical frame. From the investigation on the rate of encrustation of biofouling organisms in relation to mesh size, it was observed that the species composition of Group 1 organisms (Crypfosula, Trididemnum, I Botryllus, Symplegma and other compound tunicates) on the net of the 3 horizontal frames were different but the species composition of Group 2 organisms (barnacles, oysters, tubeworms and gastropods, etc.) on the 3 frames were similar. Itwas further noted that increase in mesh size was always accompanied by a decrease in species diversity of Group 1 organisms. On the contrary, smaller mesh net usually had more encrustation of Group 1 biofouling organisms